2013
DOI: 10.1186/1471-2369-14-122
|View full text |Cite
|
Sign up to set email alerts
|

Associations of fetuin-A and osteoprotegerin with arterial stiffness and early atherosclerosis in chronic hemodialysis patients

Abstract: BackgroundCardiovascular morbidity and mortality remains excessive in patients with chronic kidney disease. The association of vascular changes with regulators of extraosseous calcification in this patient population is still under investigation. The aim of the present study was to investigate the associations of the calcification inhibitor fetuin-A, and the anti-osteoclastic factor osteoprotegerin (OPG) with vascular pathology in chronic hemodialysis patients.MethodsIn this cross-sectional study including 81 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
25
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 51 publications
8
25
2
2
Order By: Relevance
“…This finding is in agreement with those of Moe and Chen and Wang and his colleagues, they stated that fetuin A is a potent inhibitor of vascular calcification and its low levels were associated with coronary artery calcification [52 & 53]. Also in a recent study, fetuin-A showed a significant negative association with CIMT[ [26].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is in agreement with those of Moe and Chen and Wang and his colleagues, they stated that fetuin A is a potent inhibitor of vascular calcification and its low levels were associated with coronary artery calcification [52 & 53]. Also in a recent study, fetuin-A showed a significant negative association with CIMT[ [26].…”
Section: Discussionsupporting
confidence: 82%
“…Also, our results showed a strong association between OPG levels and CIMT and valvular calcification. A recent study documented a positive association of CIMT with OPG [26]. Grzegorzewska and Mlot reported that elevated serum OPG levels were found to be correlated with the rapid progression of coronary artery calcification and mortality [55].…”
Section: Discussionmentioning
confidence: 99%
“…Our rationale for the difference in predictive value according to diabetes mellitus is as follows: first, as expected, diabetes mellitus was the most powerful predictor for MACCEs or composite outcome in our study. In other words, diabetes mellitus might overshadow biomarkers including OGN as a predictor of clinical outcomes, as presented in other studies (Pateinakis et al 2013;Scialla et al 2014). Second, CKD (Nakano et al 2013) and diabetes mellitus (Michel et al 2011) are risk factors for intraplaque hemorrhage in coronary arteries, related to the physiology of OGN.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Fetuin-A, a liver-derived inhibitor of calcification, has been inversely associated with arterial stiffness and cardiovascular morbidity and mortality. 22 Prospective studies have suggested that low serum fetuin-A concentrations may be a predictor of coronary artery disease incidence, severity, and related mortality. [23][24][25] The cardioprotective role of fetuin-A has been supported by low circulating fetuin-A concentration as a negative predictor of acute coronary disease evolution.…”
Section: Discussionmentioning
confidence: 99%